Summer on the Bluffs [compact disc, unabridged] : a novel - Hostin, Sunny; Chambers, Veronica (HarperAudio, 2021)
In the exclusive black beach community of Oak Bluffs on Martha's Vineyard, the three unofficial "goddaughters" of Amelia Vaux Tanner, successful women from different backgrounds, gather for one last summer together before Amelia moves to the south of France and gives her home to one of them.